Measurement of hydrodynamic and environmental variables in Morrocoy, Venezuela - Solana, Pedro; Castellanos, Bartolo; Nalesso, Mauro (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The results of measurements of sea level, water depth, three dimensional currents in several locations of the Morrocoy National Park, water waves and bottom temperature, as well as records of wind velocities and direction, air temperature and rainfall, during the period between May 2000 and March 2002, are shown. The analysis of the records of currents shows low intensity and dominated by the tide that interacts with the coastal system. The tide is defined as mixed, predominantly diurnal with low amplitude. The rainfall season is located between the months of June and December. The monthly average air temperature reaches their minimum during the months of January and February, where as the mean wind velocity is 4.4 m/ s with a dominant direction of E-ESE.